Pendampingan dan Pemberdayaan Keluarga dalam Pencegahan Stunting di Desa Klumpu Kecamatan Nusa Penida Kabupaten Klungkung Tahun 2024 - Sudiadnyana, I Wayan; Ruspawan, I Dewa Made; Lestari, Agus Sri; Astiti, Ni Komang Erny; Suarjana, I Made; Artawa, I Made Budi; Bekti, Heri Setiyo (Jurnal Pengabmas Masyarakat Sehat, 2025)
The problem of stunting in Nusa Penida District, especially in Klumpu Village, is still a priority. There are many factors that influence the increase in stunting cases, so an integrated approach is needed and involves community participation. The purposed of this community service is to provide assistance and empowerment to families to prevent stunting in Klumpu Village, Nusa Penida. The assistance and empowerment activities use educational booklet media designed interprofessionally by both lecturers and students of the Denpasar Ministry of Health Polytechnic. The assistance activities were carried out on 40 families and succeeded in increasing knowledge and prevention of stunting by 21.3% and attitudes by 38.4%. The results of the final evaluation of the community service activities by visiting several homes of the assistance participants showed an increase in clean and healthy living behavior (PHBS) in general, which was indicated by an increase in home sanitation conditions and the quality of family consumption patterns. The health center is expected to always provide continuous guidance and education to the community to prevent family-based stunting.